Cost-effectiveness studies in upper extremity orthopaedic surgery: A systematic review of published literature - Rajan, Prashant V. (Bone Joint J, 2018)
The goal of this study was to assess the quality and scope of the current cost-effectiveness analysis (CEA) literature in the field of hand and upper extremity orthopaedic surgery. We conducted a systematic review of MEDLINE and the CEA Registry to identify CEAs that were conducted on or after Jan 1, 1997; studied a procedure pertaining to the field of hand and upper extremity surgery; were clinical studies; and reported outcomes in terms of quality-adjusted life years. We identified a total of 33 studies that met our inclusion criteria. The quality of these studies was assessed using the Quality of Health Economic Analysis (QHES) scale. The average total QHES score for all 33 studies was 82 (high-quality). However, over time, a greater proportion of these studies have demonstrated poorer QHES quality (scores <75). Lower scoring studies demonstrated several deficits including failures in identifying reference perspectives; incorporating comparators and sensitivity analyses; discounting costs and utilities; and disclosing funding. It will be important to monitor the ongoing quality of CEA studies in orthopaedics.